ENERAPAN METODE TANYA JAWAB DENGAN TEKNIK MENUNTUN DAN MENGGALI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII SMP NEGERI 1 PURBA TAHUN PEMBELAJARAN 2016/2017 - Risma Hartati; Hertati Simanullang (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This research was carried out in SMP N 1 Purba Year 2016/2017 semester Learning Ancient odd located at Jalan Merdeka No. 16 Tiga Runggu. The subject in this study is grade VIII totaling 36 persons while the object of the research was the application of faqs for improving student learning outcomes. This type of research this is a class action research consists of two cycles. Tools used in the collection of data is a test, and teachers did and provided at the time of learning to take place to find out the results of the learning improvement of IPS students. The results showed that pre cycle data on the results of the study, IPS has an average of 36%. There are 23 students who completely (36%) fewer criteria and 23 students who do not complete (64%). On cycle I student learning results increased by an average of 53%. There are 19 students who finished (53%). Criteria that are not completely there are 17 students (47%). In cycle II, experiencing an increase of an average of 92% with and detailed contained 33 students who are finished (92%) and three students who do not complete (8%). Individually grade VIII has declared the results of the study, IPS are high after learning by using learning faqs. Keywords: Method of questioning, Learning Outcomes.